The Influence of Disaster Knowledge and Community Attitudes Towards Preparedness for Landslide Disasters in Cemparam Pakat Jeroh Village Mesidah District Bener Meriah - Rizal Rizal (UIMA Press, 2021)
Background: The high number of natural disasters in the country requires the vigilance and preparedness of all parties. Landslide events still occur in several areas in Indonesia, presumably for all parties to make preparedness and prevention efforts to face the threat of disaster. Objectives: Preparedness is an important factor that is currently the focus of attention, considering that preparedness is a determining factor for disaster risk reduction that can be carried out and pursued from an early age. Methods: This type of research is a quantitative research with a cross sectional approach. The population in this study were 207 respondents, using a random sampling technique using the Slovin formula, a sample of 68 respondents was obtained. Results: The research shows that there is an influence of disaster knowledge, community attitudes and socialization of landslides on preparedness for landslide disasters. Village Studies in Cemparam Pakat Jeroh Village, Mesidah District. Conclusion: the need for the government's role in providing business opportunities for people living in landslide-prone areas so that people can meet the needs of their family's life